The Impact of Digitizing Administrative Work in the Sultanate of Oman on Applying the Legal Principles that Govern the Functioning of Public Utilities - Albusaidi, Khalil Ben Hamad (Journal of Legal Studies and Researches, 2024)
This study reviews the extent of applying the legal principles that govern the functioning of public utilities under electronic management in the Sultanate of Oman with an indication of the effects of applying these principles and the development of these principles in the stage of electronic management, with an indication of the new legal principles that govern the functioning of electronic management.